Generalized Costs of Adjustment and Dynamic Factor Demand Theory - Mortensen, Dale T. (Econometrica, 1973)
[The properties of systems of investment equations derived under the hypothesis of present value maximization are investigated. The possibility that either the optimal time rate of change in some factor or the stationary level of some stock may increase with its own rental rate is shown to be consistent with the hypothesis in the case of more than one factor. A condition necessary for this result is that marginal products depend on the rates of which factor levels are justified.]